Modeling the Relational Complexities of Symptoms - Dolin, R. H. (Methods of Information in Medicine, 1994)
Realization of the value of reliable codified medical data is growing at a rapid rate. Symptom data in particular have been shown to be useful in decision analysis and in the determination of patient outcomes. Electronic medical record systems are emerging, and attempts are underway to define the structure and content of these systems to support the storage of all medical data. The underlying models upon which these systems are being built continue to be strengthened by a deeper understanding of the complex information they are to store. This report analyzes symptoms as they might be recorded in free text notes and presents a high-level conceptual data model representation of this domain.
Keywords: Data Display; Data Model; Computer-Based Medical Records; Natural Language; Symptoms